The Role of School Administration in Improving Operational Effectiveness and Quality of Education - Fatoni, Mahfud Heru; Fatimah, Meti; Santoso, Baron; Syarifuddin, Hamid (International Journal of Educatio Elementaria and Psychologia, 2024)
School administration plays a vital role in carrying out the core functions of educational institutions. This study aims to explore the impact of school administration on improving operational efficiency and quality of education. Using a library research approach, this study collects, analyzes, and synthesizes information from various sources to gain a comprehensive understanding of the topic. Data analysis was conducted using descriptive-qualitative methods. The findings of the study revealed that school administration plays a vital role in improving operational effectiveness and quality of education. Good management allows for efficient management of human resources, finances, and educational facilities. Schools with an organized administration system are able to create a more conducive learning environment, thus positively influencing student learning outcomes. However, challenges remain in running an effective administration. Some schools face constraints such as lack of resources, both financial and human. Therefore, it is important for related parties to collaborate and create innovative solutions to overcome these challenges.